Single-Center Retrospective Analysis of Risk Factors for Hydrocephalus After Lateral Ventricular Tumor Resection - Zhang, Chengda; Ge, Lingli; Li, Zhengwei; Zhang, Tingbao; Chen, Jincao (Frontiers in Surgery, 2022)
There is no general consensus of the placement of preoperative and intraoperative external ventricular drainage (EVD) in patients with lateral ventricular tumor(LVTs). The aim of this study was to identify the predictors of need for postoperative cerebrospinal fluid(CSF) drainage and guide the management of postoperative EVD in patients with LVTs. We performed a retrospective analysis of patients who received LVT resection at the Department of Neurosurgery, Zhongnan Hospital of Wuhan University between January 2011 and March 2021. Patients were divided between one group required CSF drainage and another group without need for CSF drainage. We analyzed the two groups to identify predictors of requirement for postoperative CSF drainage due to intracranial hypertension with clinical symptoms. A total of 97 patients met the inclusion criteria, during which 31 patients received preoperative or intraoperative EVD. 10 patients without prophylactic EVD received postoperative EVD for postoperative acute hydrocephalus. 11 patients received postoperative ventriculoperitoneal(VP)-shunt subsequently. Logistic regression analysis showed that tumor invasion of the anterior ventricle (OR =9.9), perilesional edema(OR =8.95) large volume of postoperative intraventricular hemorrhage(IVH) (OR =8.76) were independent risk factors for postoperative CSF drainage. Perilesional edema (OR =20.38) was an independent risk factor for postoperative VP-shunt due to persistent hydrocephalus. In conclusion, For patients with a LVT, those with anterior invasion, perilesional edema tend to develop acute obstructive hydrocephalus after resection, those with perilesional edema have a higher risk of shunt dependence after LVT resection.